2016
DOI: 10.1155/2016/7853787
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chemical Corrosion on the Mechanical Characteristics of Parent Rocks for Nuclear Waste Storage

Abstract: Long-term immersion was adopted to explore the damage deterioration and mechanical properties of granite under different chemical solutions. Here, granite was selected as the candidate of parent rocks for nuclear waste storage. The physical and mechanical properties of variation regularity immersed in various chemical solutions were analyzed. Meanwhile, the damage variable based on the variation in porosity was used in the quantitative analysis of chemical damage deterioration degree. Experimental results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Deng et al [25] conducted recurrent F-Tcycle experiments under the condition of H 2 SO 4 , NaOH, and NaCl solutions and pure water to investigate the coupled effect of F-T cycles and chemical solution on sandstone, and the result showed that NaOH causes stronger damage to rock samples used in these experiments than other solutions. By subjecting granite, parent rocks for nuclear waste storage, to strong acid solutions and strong alkaline solutions, Han et al [26] explored the deterioration and mechanical properties of granite under various chemistry environments and found that strong acid solutions may aggravate chemical damage deterioration in granite while strong alkaline solutions have braking effect on chemical damage deterioration in granite. Miao et al [27] used distilled water and NaCl solutions as chemistry solution to investigate granite's damage effects, aging features, and mechanisms after subjecting to solutions with different pH and flow rates.…”
Section: Introductionmentioning
confidence: 99%
“…Deng et al [25] conducted recurrent F-Tcycle experiments under the condition of H 2 SO 4 , NaOH, and NaCl solutions and pure water to investigate the coupled effect of F-T cycles and chemical solution on sandstone, and the result showed that NaOH causes stronger damage to rock samples used in these experiments than other solutions. By subjecting granite, parent rocks for nuclear waste storage, to strong acid solutions and strong alkaline solutions, Han et al [26] explored the deterioration and mechanical properties of granite under various chemistry environments and found that strong acid solutions may aggravate chemical damage deterioration in granite while strong alkaline solutions have braking effect on chemical damage deterioration in granite. Miao et al [27] used distilled water and NaCl solutions as chemistry solution to investigate granite's damage effects, aging features, and mechanisms after subjecting to solutions with different pH and flow rates.…”
Section: Introductionmentioning
confidence: 99%
“…Deep geological disposal with an engineered-barrier system (EBS) is one of the options to treat spent nuclear fuel. It aims to isolate the spent fuel from human society by sealing it in a corrosion-resistant canister and embedding permanently in the deep underground bedrock [1][2][3]. Determining the corrosion rates of canister materials exposed to a geological repository environment is an important step toward evaluating the service life of canisters in an EBS.…”
Section: Introductionmentioning
confidence: 99%
“…Yin et al [19][20][21] conducted some experimental investigation on the silt on the upstream side dam. Chen [22][23][24] calculated the lateral active earth pressure by taking unit weight of silt as a constant value.…”
Section: Introductionmentioning
confidence: 99%